Analyzing Customer Loyalty among Generation Z Food Consumers: A Systematic Review of System Quality, Ease of Use, Perceived Value, Payment Availability, and Customer Satisfaction as Mediators - Albertaadinata Albertaadinata; Sudarmiatin Sudarmiatin; Agus Hermawan (International Journal of Economics and Management Sciences, 2025)
This study conducts a Systematic Literature Review (SLR) to examine how key dimensions of digital service quality—namely system quality, ease of use, perceived value, and payment availability—shape customer loyalty among Generation Z culinary consumers, with customer satisfaction functioning as the mediating variable. Bibliometric mapping reveals that previous studies have predominantly focused on Millennials and Gen Y and have emphasized traditional service quality rather than digital service performance, indicating a significant research gap in Gen Z–specific digital consumption behavior. The SLR findings show that fast, secure, stable, and user-friendly digital systems strongly influence perceived value and user satisfaction, while the availability of digital payments such as QRIS and e-wallets enhances seamless transactional experiences. Customer satisfaction emerges as the primary psychological mechanism mediating the relationship between digital service quality and Gen Z loyalty, reflected in repeat purchases, positive word of mouth, and emotional attachment to digital culinary platforms. This study contributes theoretically by addressing existing research gaps and proposing a conceptual model of Gen Z loyalty grounded in digital experience.